Undiagnosed nevus of Оta, facial hemiparesis and esotropia: a case report - Leopoldo Garduño-Vieyra; Raúl Rúa Martínez; Isabel de la Fuente Batta (Ukrainian Society of Ophthalmologists, 2022)
Perinatal history is often underrated in ophthalmologic consultation and may provide important information in order to establish an assertive diagnosis. Purpose: To report a case of a patient who was evaluated in two hospitals as a child and misdiagnosed with Goltz syndrome. Material and Methods: it was ruled out a syndrome and the existence of three independent diagnoses was proposed: nevus of Ota, non-accommodative esotropia and left facial hemiparesis due to involvement of the VII cranial nerve. Results: A combined left eye strabismus surgery and neodymium Yag laser treatment were performed under sedation over the entire length of the nevus. Conclusion: The presence of facial palsy, strabismus or a nevus directs the physician to interrogate prenatal and perinatal issues to establish a complete diagnosis. The patient received treatment after several years and now she is satisfied.